A comparison of dynamic balance performance between non-dancers and amateur dancers across three distinct dance genres: A cross-sectional study - Ningyi Zhang; Sebastián Gómez-Lozano; Ross Armstrong; Hui Liu; Ce Guo; Alfonso Vargas-Macías (PLoS ONE, 2026)
There is controversy regarding whether dance training improves balance performance. This study aims to compare the dynamic balance performance of non-dancers and amateur dancers, as well as to examine whether differences in dynamic balance exist across various dance genres. Eighty-one participants, including 24 Flamenco dancers (FLA), 15 Latin dancers (LAT), 20 Chinese folk dancers (CHF), and 22 non-dancers as the control group (CG), completed the Y-Balance test. Anterior (YBant), posteromedial (YBpm), posterolateral (YBpl), and composite (YBcom) scores were calculated. All significant differences between groups were observed in YBcom, YBpl, and YBpm (p < 0.05), with no differences in YBant (p > 0.05). The CHF and FLA achieved higher scores compared to CG in both dominant leg (DL) and non-dominant leg (NDL), and to those of LAT in NDL for YBpm. The LAT scored slightly higher than CG (p < 0.05, d < 0.2), but it was not statistically significant. Dancers have better dynamic balance except for the YBant direction. FLA and CHF may be more effective in improving dynamic balance compared to LAT. This study was designed by considering previously contentious research findings that may be due to the distinct movement patterns and training methods of professional dancers, as well as the variations across different dance styles. The comparison of balance performance between amateur dancers, rather than professional dancers, and non-participants has significant practical implications for determining whether dance can improve an individual’s balance.